In Situ Scanning Tunneling Microscopy Study of 5,6-Dimethyl Uracil on Au (111) - Cunha,Frederico G. C. (2001)
The hydrogen evolution mediated 5,6-dimethyluracil (5,6-DMU) film disordering and subsequent reordering was studied in situ in sulfuric acid solution on Au (111) using STM and cyclic voltammetry. A stable, condensed physisorbed film was formed between the limits of the hydrogen evolution (at -0.3 V/SCE) and the lifting of the surface reconstruction (at 0.4 V/SCE) in the bulk solution concentration used in this study. The onset of hydrogen evolution led to the formation of "bubble" like structures which disrupted the stability of the film causing a disordering process which takes place within the whole scanned area. Stepping the potential back to the region of stability allowed the real time observation of the film reorganization. An anisotropic evolution of the film was found. The surface step edges were not found to be preferential nucleation sites. The molecular packing structure was inferred from high-resolution STM images and the existence of two distinct adsorbate states was established.